Implementasi Fungsi Pengorganisasian Pada Majelis Taklim Di Desa Karang Gading - Sari, Nur Fadilla; Haikal, Muhammad Fachran (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
This descriptive qualitative research aims at the implementation of the organizing function of the taklim assembly in Karang Gading village, secanggang sub-district, langkat district. Through direct observation, discussions with sources and documentation, it shows that there are two activities that are a form of implementation of the organizing function in the taklim assembly, namely the Perwiritan of Karang Gading village implements the organizational arrangements of the taklim assembly by implementing an effective line structure, so that in carrying out its duties and authorities each board has the same role and function according to their respective duties, as well as the work program that runs on the taklim assembly. The implementation of the organizing function is carried out in accordance with an Islamic perspective by referring to the Quran surah sajadah 4-5 which contains three principles of cohesiveness in one command, cooperation in good things and the division of tasks and authority.